Fecundity estimation of Indian Potasi, Neotropius atherinoides in Bangladesh - Hossian, Shajjad; Bhattacharya, Sudip; Rahman, Md Atiar; Islam, Rashedul; Yesmin, Rabeya; Sume, Salina Akhter; Moniruzzaman, Md (Research in Agriculture Livestock and Fisheries, 2020)
Fecundity estimation has obvious significance in aquaculture, since the size of brood stock, amount of rearing facilities and necessity of other equipment’s are dependent on fecundity. The study has been conducted on fecundity estimation of Indian potasi, Neotropius atherinoides, based on 202 females collected from the Kangsha River flowing through Netrokona district during the period from January to June 2013. The standard length (SL) range of female were 47-66, 50-64, 57-68, 50-66, 56-66 and 60-76 mm and range of body weight were 1.07-3.56, 1.23-3.35, 2.36-3.81, 1.69-4.31, 2.33-5.59 and 3.18-5.14 g in January, February, March, April, May and June, respectively. The mean Gonado somatic indices (GSI) were very low from January to March but these were abruptly high during subsequent three months. Based on mean GSI the spawning season of this species was assumed from April to June over the study period. Scatter plot of standard length with corresponding GSI revealed that the minimum length of mature female was 50 mm SL. Egg diameter frequency distribution of a mature ovary showed almost only one major mode of egg size suggested that the fish is a single spawner, and summation of eggs in that mode was regarded as the fecundity of a female Indian potasi. The regression equation of the relationship between standard length and fecundity was as, Fecundity = 0.0017 SL 3.55. The relative fecundity and the absolute fecundity of a fish having SL of 62 mm was 1477 per g and 3921, respectively based on F-SL relationship. The relationship between body weight and fecundity was as, Fecundity = 1371.3 BW-650.8. The absolute fecundity of a fish having BW of 3.51 g was 4162 respectively based F-BW relationship. The relationship between ovary weight and fecundity was as, Fecundity = 6244.3 OW + 967.52. The absolute fecundity of a fish having ovary weight of 3.51 g was 7211 based F-OW relationship. The correlation coefficient of all above analyses were very high (>0.755) attributing that standard length, body weight and gonad weight were highly positively correlated with fecundity of Indian Potasi, Neotropius atherinoides. Res. Agric., Livest. Fish.6(3): 421-429, December 2019